HEAT AND MONSTER BINGO: AN INSTRUCTIONAL BOARD GAME TO LEARN TEMPERATURE AND HEAT - Emilia Fandira; Anthony Wijaya; Elisabeth Prathidhina Founda Noviani (Magister Scientiae, 2018)
Physics is a subject that plays an important role in our daily life. It is a basic for the development of advanced technology. Even though it is an important subject, some high school students are not interested in learning physics. The low motivation to learn physics are caused by several reasons such as difficult material, boring classes, dislike for the teachers, and so on. Low motivation in learning physics cause negative attitude while learning physics and thus students cannot get optimal learning achievements. In this study, we developed a board game called “Heat and Monster Bingo” to make students to be interested in learning physics. The instructional game “Heat and Monster Bingo” covers topics of temperature and heat. We developed the board games in Indonesian and English so that students can learn physics in bilingual way. The broad game has gone through expert appraisal and has been tested to a group of students consisting of 27 high school students. The data were gathered through questionnaire filled by the students. According to the questionnaire data, 88.47% of the students agree that the physics learning medium in the form of board games is interesting and able to help them in studying temperature and heat.